Biblical Studies: Fifty Years of a Multi-Discipline - Davies, Philip R. (Currents in biblical research, 2014)
The creation of an autonomous and secular discipline of biblical studies can be traced back through several stages, in particular to cultural changes brought about by the Reformation and the Enlightenment. But it is only in the last 50 years or so that this discipline (more accurately, a multi-discipline) can be truly said to have emerged as distinct from Scripture, which now ought to be treated as a separate discipline belonging to theology rather than the human sciences. This review traces some of the principal themes of this discipline, specifically secularization, colonization and fictionalization. These themes are traced through a number of developments, beginning with the fundamental issue of what constitutes the ‘meaning’ of a text. Finally, it is suggested that the relationship between humanistic biblical studies and theological Scripture is becoming, and will continue to be, more explicitly addressed, but that no clear resolution can be foreseen.